GAMBARAN RESESI GINGIVA PADA PASIEN PENGGUNA NARKOBA (Penelitian) - Aisy Kahla Nugraha Putri Kahla Nugraha Putri; Lies Zubardiah (Fakultas Kedokteran Gigi Universitas Trisakti, 2019)
Background. Drugs or addictive compounds used for specific cases are prescribed by physicians and doctors. However, the drugs being illegally misused can cause several health issues including oral health complications. Study shows that abusive drugs can result in periodontal problems which could lead to loss of attachment. Objectives. To assess the degree of gingival recession in drug rehabilitation patients at RSKO. Method. Thirty rehabilitation patients at RSKO Jakarta were observed in the distribution of gingival recession in anterior teeth over clinical photographs. The findings of gingival recession were grouped according to Miller's classification. Gingival recession was observed based on history of oral hygiene maintenance, type of drug, and length of time of drug use. Results. Based on Miller's classification, it was found that grade I gingival recession was 63% and grade II was 38% in patients with poor oral hygiene status. Grade III gingival recession was found in patients with deficiences oral hygiene status. Patients with a history of using mixed drugs had a higher risk of experiencing gingival recession (63%). Grade III gingival recession was mostly found in patients with a history of consuming more than one type of drug (60%), and had taken drugs for more than 5 years (80%). Conclusion. Gingival recession was found more in patients with a history of drug abuse and poor oral hygiene.